Can blockchain solve the hold-up problem in contracts? - Holden, Richard T., 1974-; Malani, Anup (Cambridge : Cambridge University Press, 2021)
A vexing problem in contract law is modification. Two parties sign a contract but before they fully perform, they modify the contract. Should courts enforce the modified agreement? A private remedy is for the parties to write a contract that is robust to hold-up or that makes the facts relevant to modification verifiable. Provisions accomplishing these ends are renegotiation-design and revelation mechanisms. But implementing them requires commitment power. Conventional contract technologies to ensure commitment - liquidated damages - are disfavored by courts and themselves subject to renegotiation. Smart contracts written on blockchain ledgers offer a solution. We explain the basic economics and legal relevance of these technologies, and we argue that they can implement liquidated damages without courts. We address the hurdles courts may impose to use of smart contracts on blockchain and show that sophisticated parties' ex ante commitment to them may lead courts to allow their use as pre-commitment devices.
Title from publisher's bibliographic system (viewed on 27 Oct 2021).
Keywords: Contracts -- Economic aspects; Blockchains (Databases)